A Sadd adz-Dzari'ah Analysis of Legal Differences in the Marriage of Out-of-Wedlock Pregnant Women: A Comparative Study of the Shafi'i and Hanbali Schools - Muhammad Rifqi Ramadhianto; Emha Hasan Nashrulloh Asy'ari (Program Pascasarjana UIN Sumatera Utara, 2026)
The high rate of out-of-wedlock pregnancy in Indonesia represents a social problem requiring a comprehensive legal response. Article 53 of the Compilation of Islamic Law permits the marriage of pregnant women without waiting for childbirth following the Shafi'i school, while the Hanbali school prohibits it until the woman gives birth and fulfills repentance requirements. Previous studies have compared the positions of both schools descriptively but have not explained the epistemological roots of their differences. This study aims to analyze how the Shafi'i and Hanbali schools construct their legal positions on the marriage of out-of-wedlock pregnant women and to explain their differences through the framework of Sadd adz-Dzari'ah. The method employed is juridical-normative library research using comparative and conceptual approaches, drawing on primary fiqh and usul al-fiqh texts of both schools. This study finds that the difference between the two schools is epistemological: the Shafi'i school categorizes such marriage as dzari'ah qalilah because the harm of zina is considered to have already occurred and the nasab relationship is legally severed, while the Hanbali school categorizes it as dzari'ah ghalibah because the ease of marriage during pregnancy is seen as dominantly weakening the deterrence function of Islamic law at the social level. These findings fill the gap left by previous descriptive-comparative studies and offer an analytical model based on Sadd adz-Dzari'ah typology replicable for similar jurisprudential issues. Practically, this study provides an argumentative basis for evaluating the preventive dimension of KHI Article 53.